An ontology for managing network services quality - Rodrigues, Carlos (2012)
The evolution of IP networks to a service-oriented paradigm poses new challenges to service providers regarding the management and auditing of network services. The upward trend in ubiquity, heterogeneity and virtualization of network services and resources demands for a formal and systematic approach to network management tasks. In this context, the semantic characterization and modeling of services provided to users is a key component to sustain autonomic service management, service negotiation and configuration. The semantic and formal description of services and resources is also relevant to assist paradigms such as cloud computing, where a large diversity of resources have to be described and managed in a highly dynamic way. This paper defines an ontology for multiservice IP networks targeting multiple service management goals, namely: (i) to foster client and service provider interoperability; (ii) to manage network service contracts, promoting the dynamic negotiation between parties; (iii) to access and query SLA/SLSs data on a individual or aggregated basis to assist service provisioning in the network; and (iv) to sustain service monitoring and auditing. A ServiceModel API is provided to take full advantage of the proposed semantic model, allowing Service Management Platforms to access the ontological contents. This ontological development takes advantage of SWRL to discover new knowledge, enriching the possibilities of systems described using this support.